2008
DOI: 10.1007/s00120-008-1825-z
|View full text |Cite
|
Sign up to set email alerts
|

Das Transitionalzellkarzinom der Harnblase

Abstract: Up to now markers for transitional cell carcinoma of the bladder (TCC) are missing. Fibronectin (FN) seems to play a key role in progression and invasion of malignant tumors. The aim of this study was to assess the value of cellular FN (cFN), a more specific subform of produced FN, in different stages of TCC.cFN was determined using a highly sensitive immunoassay which we developed. Blood samples were taken of 45 patients with the first diagnosis of TCC before undergoing TUR-B and 6 patients with metastatic TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Fibronectin is a glycoprotein with a mo lecular weight of 440 kDa, found in soluble form in plas ma and other body fluids, and in an insoluble (matrix) form in basement membranes and the extracellular matrix. Fibronectin (FN) seems to play a key role in progression and invasion of malignant tumors (10) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fibronectin is a glycoprotein with a mo lecular weight of 440 kDa, found in soluble form in plas ma and other body fluids, and in an insoluble (matrix) form in basement membranes and the extracellular matrix. Fibronectin (FN) seems to play a key role in progression and invasion of malignant tumors (10) .…”
Section: Introductionmentioning
confidence: 99%
“…BCG ce lls possess specific high-affinity receptors to fibronectin molecules (9) . The initial crucial step in BCG therapy seems to be the binding of mycobacteria to the urothelial lining which depends on the interaction of a fibronectin attachment protein (FAP) on the bacterial surface with the fibronectin in the bladder wall (10) . In vitro studies showed that a stable BCG/ fibronectin interaction was dependent on FAP binding to fibronectin (9) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations